Moldova : Technical Assistance Report on Taking Compliance Management Further. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This report concerns the delivery of a tax administration mission to Moldova during February 8 - 21, 2012 by the Fiscal Affairs Department (FAD) of the IMF as a component of implementing FAD's technical assistance strategy for Southeast Europe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet